Management of an unusual peripheral giant cell granuloma: A diagnostic dilemma - Satheesh Mannem; Vijay K Chava (Wolters Kluwer Medknow Publications, 2012)
The peripheral giant cell granuloma (PGCG) is a reactive exophytic lesion of the gingiva and alveolar ridge that usually occurs as a result of local irritating factors such as plaque, calculus, chronic infections, chronic irritation, tooth extraction, improperly finished fillings, unstable dental prosthesis, and impacted food which originates from the periosteum or periodontal ligament. This article presents management of an unusual PGCG located on the partially edentulous mandible.